Consumption-Based Interest Rate and the Present-Value Model of the Current Account-Evidence from Nigeria - Adedeji, Olumuyiwa (IMF Working Papers; Working Paper, 2001)
This paper presents a model of current account determination, based upon the permanent-income hypothesis. A present-value relationship among the current account, changes in net output, the exchange rate and the terms of trade is derived and the implications of such a relationship are tested using data for Nigeria during 1960-97. This paper presents a model of current account determination, based upon the permanent-income hypothesis. A present-value relationship among the current account, changes in net output, the exchange rate and the terms of trade is derived and the implications of such a relationship are tested using data for Nigeria during 1960-97.